Workflow temporal verification for monitoring parallel business processes‡. Issue 4 (8th January 2016) - Liu, Xiao; Wang, Dingxian; Yuan, Dong; Wang, Futian; Yang, Yun
Abstract: Workflow temporal verification is conducted to guarantee on‐time completion, which is one of the most important QoS (Quality of Service) dimensions for business processes running in the cloud. However, as today's business systems often need to handle a large number of concurrent customer requests, conventional response‐time based process monitoring strategies conducted in a one‐by‐one fashion cannot be applied efficiently to a large batch of parallel processes because of significant time overhead. Similar situations may also exist in software companies where multiple software projects are carried out at the same time by software developers. To address such a problem, based on a novel runtime throughput consistency model, this paper proposes a QoS‐aware throughput based checkpoint selection strategy, which can dynamically select a small number of checkpoints along the system timeline to facilitate the temporal verification of throughput constraints and achieve the target on‐time completion rate. Experimental results demonstrate that our strategy can achieve the best efficiency and effectiveness compared with the state‐of‐the‐art as and other representative response‐time based checkpoint selection strategies. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Current response‐time based checkpoint selection and temporal verification strategies for a single scientific workflow cannot be applied directly to the monitoring of a large batch of parallel processes. To address such an issue, we have investigated the measurement of workflow throughput and proposed a QoS‐aware throughput‐based temporal checkpoint selection and verification strategy. Experimental results demonstrated that our strategy can achieve the best efficiency and effectiveness compared with the state‐of‐the‐art and other representative response‐time based checkpoint selection strategies.